Concentrations of MUC16 and MUC5AC using three tear collection methods - Ablamowicz, Anna F; Nichols, Jason J (Molecular vision, 2017)
To determine the optimal tear collection method for analysis of ocular surface mucins MUC5AC and MUC16. Fifteen subjects without ocular surface disease were recruited. Subjects presented for tear collection on three separate days for three different tear collection methods with the order of method randomized. Methods used to collect tears from right and left eyes included Schirmer's strip, basal tear collection, and flush tear collection. All samples from the right eyes were individually analyzed for MUC5AC whereas the left eye samples were individually analyzed for MUC16. For each individual sample, 10 μg of protein were loaded per lane into a 1% (w/v) agarose gel and run in electrophoresis buffer for 2 h. After overnight capillary transfer, membranes were incubated with either MUC5AC antibody CLH2 or MUC16 antibody OC125 for western blot analysis. Blots were developed with enhanced chemiluminescence (ECL) and signals captured with the Odyssey Fc (LI-COR). The relative amounts of MUC5AC and MUC16 were quantified with densitometry using software and compared for statistically significant differences between tear collection methods using the Kruskal-Wallis test in SPSS 22 and GraphPad Prism 7.02. Dunn's multiple comparisons test was used for pairwise post-hoc comparisons. Samples containing less than 10 μg of total protein were not used for analysis which left eight samples (out of 45) unusable. The calculated MUC5AC median signal intensities from Schirmer's strip, basal tears, and flush tears were 2.86 (n = 15, the interquartile range [IQR] = 2.54-3.21), 1.65 (n = 14, IQR = 1.34-3.1), and 1.67 (n = 9, IQR = 1.42-1.72), respectively (H = 9.5, p = 0.009). Post-hoc pairwise comparisons showed a statistically significant difference between Schirmer's strip and flush tears (p = 0.01). The calculated MUC16 median signal intensities from Schirmer's strip, basal tears, and flush tears were 1.88 (n = 14, IQR = 1.43-2.61), 5.24 (n = 15, IQR = 4.16-6.21), and 2.45 (n = 7, IQR = 1.85-2.48), respectively (H = 18.1, p = 0.001). Post-hoc pairwise comparison showed statistically significant differences between basal tears and Schirmer's strip (p = 0.0003) and between basal tears and flush tears (p = 0.006). MUC5AC and MUC16 are present in human tear fluid and can be captured using various tear collection methods. Although basal tear collection yielded the highest relative concentration of MUC16, Schirmer's strip tear collection yielded the highest MUC5AC concentration. Therefore, the tear collection method chosen depends on the mucin of interest.